Study of Mangrove Forest Existing Condition using Remote Sensing Image in The Karawang Coast of 2018 - R. Ade Komarudin; Aris Kabul Pranoto; Dian Sutono; Anthon Anthonny Djari (PELAGICUS, 2021)
ABSTRACTThe northern part of Karawang is a coastal area with mostly mud-sand substrates. This substrate tends to be unstable, so that naturally, this kind of sediment is supported by coastal vegetation that forms coastal ecosystems, such as mangroves; therefore, the importance of mangroves in Karawang coast is definite. Unfotunately the data regarding the condition of mangroves in Karawang Regency is quite insufficient. This information, especially about its existence, is needed as a database for further research and as basis to support government policies on coastal area management. The aim of this research is to provide information about the existence of mangrove in Karawang Regency. The method is by using Normalized Different Vegetation Index (NDVI) calculations on Landsat 8 2018 satellite imagery of Karawang to get the data that reveal the information. We have discovered that the existing of mangroves in Karawang Regency in 2018  is 305,14 Ha. Border coast that is vegetated is only 33.75 km of 77 km long coastline of Karawang. Only less than 5% of the total mangrove protected area in Karawang Regency is detected as mangrove from the total 9.055 Ha of the area.